Analisis Pertumbuhan Ekonomi Daerah Provinsi Jambi - Nurdin Nurdin (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
This study uses secondary data collected by the object of research in Jambi Province in the form of factors affecting the economic growth of Jambi Province sourced from the Central Bureau of Statistics (BPS). Data were collected during the period 2004 to 2015. The purpose of this study is to analyze and know what factors affect the economic growth of Jambi Province period 2004-2015. The analytical tool used is this research using econometric analysis tool with Ordinary Least Square (OLS) method with multiple linear regression equation through the aid of SPSS software program. 21:00. Based on the discussion of data analysis results in this study, it can be concluded the result of R-squared calculation shown in the above equation obtained R2 value of 0.989. This shows that about 98.90 percent of the upturned economic growth (Yt) in Jambi Province is influenced by investment variable (X1t), capital expenditure (X2t), working population (X3t), unemployment (X4t) and poverty (X5t). While the remaining 1.10 percent, explained by other variables that are not included into the regression equation. Keywords: Economic Growth, Investment, Capital Expenditure, Working Population, Unemployment And Poverty